Experimental Infestation of rabbits with Amblyomma Variegatum larvae:host effects on larval yield, engorged weight and engorgement period. (1990)
Rabbits infested Amblyomma variegatum larvae were not able to acguire a resistance which effectively inhibited their feeding. There was no significant diiference in "larval yeild",engrogement period of the larvae harvested from the primary, secondary and tertiary infestations. While enviromental tempreture had a marked influence on the "larval yeild", engorged weight and engorgement period of the larvae, the sex of the rabbits did not affect them.